Compressive creep behavior of hot-pressed GeTe based TAGS-85 and effect of creep on thermoelectric properties. (1st October 2018) - Chang, M.C.; Agne, M.T.; Michi, R.A.; Dunand, D.C.; Snyder, G.J.
Abstract: Thermoelectric materials often operate at high homologous temperatures where they can be subjected to sizeable internal and external stresses, making them prone to creep deformation over long periods of use. Hot-pressed (GeTe)85 (AgSbTe2 )15 (TAGS-85) exhibits a fine grain size averaging ∼8 μm – of concern for creep resistance - with 70% of the grains below 10 μm and 30% between 10 and 150 μm; second phase Ag8 GeTe6 particles, ∼2 μm in size, are also present at grain boundaries. Strain rates of TAGS-85 under a series of stresses are measured at 375–425 °C. By fitting the creep data to a power law creep equation, the stress exponent n and activation energy Q for creep are determined to be n = 2.6 ± 0.1 (<12 MPa applied stress) or n = 3.7 ± 0.4 (>12 MPa applied stress) and Q = 157 ± 2 kJ/mol, respectively. Thermoelectric measurements show 15% lower electrical conductivity and ∼30% higher lattice thermal conductivity after creeping to 10% strain. The evolution of ambient-temperature electrical conductivity and thermal conductivity for a single sample crept at intervals of 2% strain is consistent with the expectation that dislocations accumulate during primary creep while annealing effects may reduce subgrain boundaries that scatter phonons. Graphical abstract: Image 1